2021
DOI: 10.3390/pharmacy9040202
|View full text |Cite
|
Sign up to set email alerts
|

Interventional, Quasi-Experimental Study of a Chronic Obstructive Pulmonary Disease Education Care Plan for Hospital Discharge

Abstract: Chronic obstructive pulmonary disease (COPD) is one of the leading causes of morbidity, mortality, and reduced quality of life for patients. Proper use of inhaler devices is critical for effective drug delivery and prevention of COPD progression. The primary endpoint of this study was a mean percent increase in correct steps associated with inhaler technique after pharmacist education. The co-primary endpoint was a 25% increase in the proportion of patients correctly identifying the appropriate use of short-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Other studies involved pharmacists focusing on fewer aspects of the care bundle, for example, smoking cessation, 21 educating nurses, 10 inhaler technique education, 16,22 developing standardized education tools, 11 medication reconciliation at discharge, 14 preparing discharge medication packages, 9 or a combination of these 6,12,13 In a meta-analysis including eight studies with over 1800 participants, inhaler technique education showed a significant reduction in exacerbations (pooled risk ratio = 0.71; 95% confidence interval, 0.59-0.86; p < 0.001). 24 A study by Warunek and colleagues 16 found that patient education by pharmacists improved patient inhaler technique and knowledge. This study emphasizes that inhaler technique education by a pharmacist leads to improved, accurate use after 48 h. Increased adherence and using the appropriate inhalers at the correct time can contribute to improved symptoms and decreased exacerbations.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Other studies involved pharmacists focusing on fewer aspects of the care bundle, for example, smoking cessation, 21 educating nurses, 10 inhaler technique education, 16,22 developing standardized education tools, 11 medication reconciliation at discharge, 14 preparing discharge medication packages, 9 or a combination of these 6,12,13 In a meta-analysis including eight studies with over 1800 participants, inhaler technique education showed a significant reduction in exacerbations (pooled risk ratio = 0.71; 95% confidence interval, 0.59-0.86; p < 0.001). 24 A study by Warunek and colleagues 16 found that patient education by pharmacists improved patient inhaler technique and knowledge. This study emphasizes that inhaler technique education by a pharmacist leads to improved, accurate use after 48 h. Increased adherence and using the appropriate inhalers at the correct time can contribute to improved symptoms and decreased exacerbations.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other studies looking at COPD care bundles, this is the first study that has expanded the role of the pharmacist in the inpatient setting to provide a more comprehensive approach to patient care. Other studies involved pharmacists focusing on fewer aspects of the care bundle, for example, smoking cessation, 21 educating nurses, 10 inhaler technique education, 16,22 developing standardized education tools, 11 medication reconciliation at discharge, 14 preparing discharge medication packages, 9 or a combination of these 6,12,13 with varying results. The single pharmacist in this study was able to intervene and contribute to patient care in a variety of different ways such as conducting accurate medication histories, assessing a patient's GOLD classification, recommending adjustments to COPD related therapies, providing inhaler technique education, immunization education, disease state counseling, and discharge counseling.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations